2023
DOI: 10.1021/jacs.3c05948
|View full text |Cite
|
Sign up to set email alerts
|

Selective Protein of Interest Degradation through the Split-and-Mix Liposome Proteolysis Targeting Chimera Approach

Chunli Song,
Zijun Jiao,
Zhanfeng Hou
et al.

Abstract: Proteolysis Targeting Chimera (PROTAC) technology represents a promising new approach for target protein degradation using a cellular ubiquitin-proteasome system. Recently, we developed a split-and-mix nanoplatform based on peptide self-assembly, which could serve as a self-adjustable platform for multifunctional applications. However, the lower drug efficacy limits further biomedical applications of peptide-based SM-PROTAC. In this study, we develop a novel split-and-mix PROTAC system based on liposome self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Another reason could be that the orientation of functional molecules in the assembly process cannot be controlled in the current stage. To solve these problems, we are actively exploring the construction of programmable degradants based on liposomes or polymers . In conclusion, our work uncovered the promising potential of the split-and-mix platform in the realm of lysosome-based degraders, which may efficiently provide useful lysosome-based drugs for clinical applications.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another reason could be that the orientation of functional molecules in the assembly process cannot be controlled in the current stage. To solve these problems, we are actively exploring the construction of programmable degradants based on liposomes or polymers . In conclusion, our work uncovered the promising potential of the split-and-mix platform in the realm of lysosome-based degraders, which may efficiently provide useful lysosome-based drugs for clinical applications.…”
Section: Discussionmentioning
confidence: 90%
“…To confirm the degradation activity of SM-CMAD, ERα was selected as the targeted protein, which was a common target for protein degraders. 20 We constructed an ERα degrader (KFERQ+TMXF-θθ (1:1)) by coassembling an ERα recruitment module (TMXF-δδRR) and a lysosome targeting module (KFERQ-Ahx-δδRR) within a nanoparticle (Figures 2A, S1−3). To confirm the degradation ability of KFERQ+TMXF-θθ (1:1), we analyzed the ERα protein level in T47D cells after 24-h incubation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The most common lipid-based nanoparticles are spherical platforms that contain at least one lipid bilayer containing at least one internal aqueous compartment. The use of phospholipids and sterols is considered beneficial for PROTAC drug administration 33,46–52 since these compounds are analogous to cellular membranes and facilitate cellular uptake. 53 At the same time, the modification flexibility of basic liposome components endows PROTACs with the capability of tissue-targeting 50 and controlled release.…”
Section: Delivery Systems and Protac Drug Loadingmentioning
confidence: 99%
“…The split-and-mix PROTAC approach is employed as a special nanoplatform capable of facile screening and self-optimized biomolecule regulation. 15,47,91–95 Specifically, this system consists of independent hydrophilic segments with recruiting targets of POIs and E3 ligases respectively. This strategy (Fig.…”
Section: Split-and-mix Protac Approach and Center-spoke Degradation N...mentioning
confidence: 99%
“…Peptide-based PROTAC drugs have emerged as a promising alternative solution for various targets. In order to enhance the clinical potential of ARTC, we propose utilizing a peptide double-stapling strategy to stabilize both the α-helical and β-sheet peptide motifs. Previous studies have demonstrated that double-stapled peptides can exhibit significantly improved proteolytic stability and enhanced biological activities compared to their linear counterparts .…”
Section: Introductionmentioning
confidence: 99%